2020
DOI: 10.1016/j.psychres.2020.113323
|View full text |Cite
|
Sign up to set email alerts
|

The connection and background mechanisms of social fears and problematic social networking site use: A structural equation modeling analysis

Abstract: Highlights Self-esteem and social anxiety only indirectly predicted problematic social networking site (SNS) use and problematic internet use (PIU). Fear of negative evaluation mediated associations between social anxiety and self-esteem and both PIU and problematic SNS use. These indirect pathways might also highlight relevant differences behind the motivation of PIU – anonymity – and problematic SNS use – control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 53 publications
1
6
1
Order By: Relevance
“…Our study supports the Interaction of Person-Affect-Cognition-Execution (I-PACE) model (Brand et al, 2016(Brand et al, , 2019, Social Compensation Hypothesis (Weidman et al, 2012), and the Compensatory Internet Use Theory (Kardefelt-Winther, 2014), such that high fear of negative evaluation favours CMC over FTF interactionsindicated by high ratings on problematic internet and social network site use -as a compensatory behavior to deal with low self-esteem and high social anxiety. In line with previous studies, this study confirmed that highly socially anxious individuals prefer using CMC over FTF as it reduces their anxiety and stress levels (Van Deursen et al, 2015;Zsido et al, 2020Zsido et al, , 2021.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study supports the Interaction of Person-Affect-Cognition-Execution (I-PACE) model (Brand et al, 2016(Brand et al, , 2019, Social Compensation Hypothesis (Weidman et al, 2012), and the Compensatory Internet Use Theory (Kardefelt-Winther, 2014), such that high fear of negative evaluation favours CMC over FTF interactionsindicated by high ratings on problematic internet and social network site use -as a compensatory behavior to deal with low self-esteem and high social anxiety. In line with previous studies, this study confirmed that highly socially anxious individuals prefer using CMC over FTF as it reduces their anxiety and stress levels (Van Deursen et al, 2015;Zsido et al, 2020Zsido et al, , 2021.…”
Section: Discussionsupporting
confidence: 91%
“…According to Caplan (2002), anonymity and control over social situations are two major features of CMC. The extensive use of the internet and social media is one of the major reasons for several social problems young adults (18 to 25 years) face in technologically sophisticated countries (Arrivillaga et al, 2020a(Arrivillaga et al, , 2020b(Arrivillaga et al, , 2021Zsido et al, 2020).…”
Section: Computer-mediated Communicationmentioning
confidence: 99%
“…Finally, people suffering from these psychiatric disorders, more specifically emotional disorders, are more prone to develop addictive disorders such as PSMU [ 23 ]. To boot, previous results indicated that social anxiety lead to favoring computer mediated over face to face communication [ 24 ]. Reciprocally, individuals with greater PSMU levels neglect some aspects of their lives thus contributing to the development of depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…This can result in negative effects with regards to stress levels and sleep [14], disturbance, economic problems and cognitive or antisocial disorders [15]. In this sense, there are several papers showing that smartphone addiction can have serious health consequences related, especially, to the fear of missing out and social anxiety [16][17][18]. Even from a theoretical perspective, problematic smartphone use is described as a multifaceted phenomenon that is manifested in a variety of dysfunctional ways, such as addictive use and antisocial behaviours.…”
Section: Introductionmentioning
confidence: 99%